Curtains Marketing Analysis on Cv. Chantika Gorden Palu - Djamal, Astrid Susanti; Sirajudin, Sirajudin; T., Sarifuddin, (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Based on the results of the analysis carried out by comparing the target and the realization achieved by CV. Chantika Gorden Palu in controlling the efficiency of marketing activities shows that in 2016 salesperson activities amounted to 27.69%, which means salesperson activities at CV. Chantika Gorden Palu in 2016 was less efficient, while sales promotion activities of 25.83% indicated that sales promotion activities were also less efficient, while advertising activities were efficient with a value of 5.83%. Control of CV marketing activities. Chantika Gorden Palu in 2017 for salesperson activities 11.93% which means that it is quite efficient, then for sales promotion activities it is 24.17% which means sales promotion activities are less efficient, while for advertising activities it is 4.17% which means that advertising activities 2017 is very efficient. Control of CV marketing activities. Chantika Gorden Palu in 2018 for salesperson activities of 39.84% and sales promotion of 35% which means inefficient, while for advertising activities it is 4.17% which means that advertising activities in 2018 are less efficient.